Prevalence and outcomes of renal transplantation in children with intellectual disability. (19th August 2014) - Wightman, Aaron; Young, Bessie; Bradford, Miranda; Dick, André; Healey, Patrick; McDonald, Ruth; Smith, Jodi
Abstract To describe the prevalence and outcomes of renal transplantation in children with ID we performed a retrospective cohort analysis of all children receiving a first kidney‐alone transplant in the UNOS dataset from 2008 to 2011. Recipients with definite, probable, and without ID were compared using chi‐square tests. Kaplan–Meier curves were constructed for patient and graft survival. Cox proportional hazard models were used to estimate the association between ID and graft failure and patient survival. Over the study period, 332 children with definite (117) or probable (215) ID underwent first renal transplant, accounting for 16% of all first pediatric renal transplants (n = 2076). Children with definite ID were not significantly different from children without ID with respect to sex, ethnicity, or prevalence of acute rejection. ID was associated with increased likelihood of deceased donor source. ID was not significantly associated with decreased graft or patient survival. In this first large‐scale study, up to 16% of first pediatric renal transplants were performed in children with ID. Short‐term graft and patient survival after transplant were equivalent between children with and without ID. Further research is needed to examine long‐term outcomes of transplant in this population.